2019
DOI: 10.1371/journal.pmed.1002996
|View full text |Cite
|
Sign up to set email alerts
|

Elective and nonelective cesarean section and obesity among young adult male offspring: A Swedish population–based cohort study

Abstract: BackgroundPrevious studies have suggested that cesarean section (CS) is associated with offspring overweight and obesity. However, few studies have been able to differentiate between elective and nonelective CS, which may differ in their maternal risk profile and biological pathway. Therefore, we aimed to examine the association between differentiated forms of delivery with CS and risk of obesity in young adulthood.Methods and findingsUsing Swedish population registers, a cohort of 97,291 males born between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 68 publications
0
46
0
Order By: Relevance
“…Basing on the obtained results the issue of the participation of the microbiota in the development of obesity should be further discussed [51]. Ahlqvist, et al [78] found no evidence of an association between elective or nonelective cesarean section and young adulthood obesity in young male conscripts when accounting for maternal and paternal factors (relative risk ratio RRR = 0.96; CI 95% 0.83-1.10). Authors suggested there is no clinically relevant association between cesarean section and the development of obesity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Basing on the obtained results the issue of the participation of the microbiota in the development of obesity should be further discussed [51]. Ahlqvist, et al [78] found no evidence of an association between elective or nonelective cesarean section and young adulthood obesity in young male conscripts when accounting for maternal and paternal factors (relative risk ratio RRR = 0.96; CI 95% 0.83-1.10). Authors suggested there is no clinically relevant association between cesarean section and the development of obesity.…”
Section: Discussionmentioning
confidence: 97%
“…A summary of the search process is illustrated in Figure 2, as recommended by the PRISMA guidelines [90]. Due to sufficient data regarding the occurrence of respiratory tract infections, asthma, overweight/obesity as well as diabetes mellitus type 1, 16 articles [11,20,67,68,[70][71][72][73][74][75][76][77][78][79][80][81]85,86,88,89] were included in the meta-analysis. for those citations considered potentially relevant and assessed for eligibility by the two researchers.…”
Section: Study Selection Processmentioning
confidence: 99%
“…Two previous studies were conducted with male individuals in late adolescence, verifying an association among cesarean delivery and obesity measured by BMI: Bar-Meir et al 27 evaluated 17,003 17-year-olds individuals in West Jerusalem, and Svensson et al 28 studied 21,051 18-year-old individuals in Denmark. Two other studies were found that did not verify this association: Barros et al 5 who studied fat mass index assessed by DXA in 3961 adolescents aged 18 years in the city of Pelotas in Rio Grande do Sul, Brazil, and the study by Ahlqvist et al 29 who studied BMI in 97,291 men with an average age of 18 years from Sweden. These studies do not point to a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the association between cesarean delivery and obesity have been done including children 4,5,6,17,32,33,34,35,36,37,38 and adults 5,16,39,40,41 . Some studies have been carried out including adolescent individuals 4,5,6,17,42 , but there are few studies conducted with individuals in their late adolescence 4,5,27,29 . This study was carried out with people in this age group because they have already gone through the growth stage and are no longer under the hormonal effects of adolescence, which provide greater deposition of adipose tissue 43 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other, maternal medical histories of CS are associated with persistent severe obstetric risks in later pregnancies as well as with an excess maternal morbidity burden 9 17 . Epidemiological studies have shown associations between birth by CS with excess risks of a range of offspring morbidities each capable of adversely impacting cardiorespiratory fitness (CRF) later in life 10 , 18 23 . If CS is a causal factor in such morbidities, it is possible that CS would impact CRF.…”
Section: Introductionmentioning
confidence: 99%